Scoping Review of Elasticity and Tax Effort of Hotel and Restaurant Taxes on Regional GDRP in Indonesia - Siti Aulia Azmi; Abdul Manan; Endang Astuti (Future Techno-Science, 2025)
Hotel and restaurant tax is one of the sources of Local Revenue (PAD) that has a strategic role in regional economic development. This study aims to review the literature related to the collection mechanism, challenges, and impact of hotel and restaurant tax on the growth of the tourism sector and the regional economy. The results of the literature review indicate that this tax not only functions as a fiscal instrument to increase regional revenue, but also as a regulatory tool in managing the hotel and culinary sectors. However, various challenges such as low levels of tax compliance, weak supervision, and the potential for tax leakage are still obstacles in optimizing regional tax revenues. Therefore, a balanced policy is needed between increasing the effectiveness of tax collection and providing incentives for business actors so that this sector continues to develop sustainably. With a good tax management system, hotel and restaurant tax can contribute significantly to driving local economic growth and supporting more inclusive and sustainable regional development.